The Effect of Different Verses and Reading Styles of Quran Recitation on Relaxation Among University Students - Eman Ghanim; Muhammad Nubli Abdul Wahab; Yasir H. Naif (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – Despite the predominance of Muslim students at Universiti Malaysia Pahang, the psychological effects of Quran recitation on stress and relaxation remain insufficiently investigated using scientific measures. Therefore, this study addresses this gap by examining the relaxation effects of Quran recitation through biofeedback analysis. Design/methods/approach – Repeated measures mixed quasi-experimental design was conducted in this study. For heart rate variability (HRV) test, thirty undergraduate students who participated in this test were divided into two groups: good Quran reciters group and weak Quran reciters group based on recitation test. And for breathing behavior (BB) test, six undergraduate students are good Quran reciters who are involved in this test. Findings – Pre–post test score means differences comparison showed significant differences in HRV, when all p-values < 0.05 for both groups. And the results between good reciters group and weak reciters group also shows a clear significant difference in HRV data when all p-values < 0.05. So, students who are proficient in reciting the Quran can more easily control their psychological signals than those who are not, which tends to promote relaxation. Research implications/limitations –The emWave PC tool and the CapnoTrainer have been used to measure HRV and BB. Originality/value – this research is to examine the effects of Quran recitation and reading styles (Tajweed, Story, Theme, and Understanding) on the Heart Rate Variability (HRV) and Breathing Behavior (BB) among undergraduate university students and their relaxation.